Inducible deletion of raptor and mTOR from adult skeletal muscle impairs muscle contractility and relaxation. (10th November 2022) - Baraldo, Martina; Zorzato, Sabrina; Dondjang, Achille Homère Tchampda; Geremia, Alessia; Nogara, Leonardo; Dumitras, Ana Georgia; Canato, Marta; Marcucci, Lorenzo; Nolte, Hendrik; Blaauw, Bert
Abstract : Abstract: Skeletal muscle weakness has been associated with different pathological conditions, including sarcopenia and muscular dystrophy, and is accompanied by altered mammalian target of rapamycin (mTOR) signalling. We wanted to elucidate the functional role of mTOR in muscle contractility. Most loss‐of‐function studies for mTOR signalling have used the drug rapamycin to inhibit some of the signalling downstream of mTOR. However, given that rapamycin does not inhibit all mTOR signalling completely, we generated a double knockout for mTOR and for the scaffold protein of mTORC1, raptor, in skeletal muscle. We found that double knockout in mice results in a more severe phenotype compared with deletion of raptor or mTOR alone. Indeed, these animals display muscle weakness, increased fibre denervation and a slower muscle relaxation following tetanic stimulation. This is accompanied by a shift towards slow‐twitch fibres and changes in the expression levels of calcium‐related genes, such as Serca1 and Casq1 . Double knockout mice show a decrease in calcium decay kinetics after tetanus in vivo, suggestive of a reduced calcium reuptake. In addition, RNA sequencing analysis revealed that many downregulated genes, such as Tcap and Fhod3, are linked to sarcomere organization. These results suggest a key role for mTOR signalling in maintaining proper fibre relaxation in skeletal muscle. Key points: Skeletal muscle wasting and weakness have been associated with different pathological conditions, including sarcopenia and muscular dystrophy, and are accompanied by altered mammalian target of rapamycin (mTOR) signalling. Mammalian target of rapamycin plays a crucial role in the maintenance of muscle mass and functionality. We found that the loss of both mTOR and raptor results in contractile abnormalities, with severe muscle weakness and delayed relaxation following tetanic stimulation. These results are associated with alterations in the expression of genes involved in sarcomere organization and calcium handling and with an impairment in calcium reuptake after contraction. Taken together, these results provide a mechanistic insight into the role of mTOR in muscle contractility. Abstract : Abstract figure legend By taking a genetic loss‐of‐function approach, we demonstrate that mammalian target of rapamycin (mTOR) plays an important role in muscle homeostasis and contractility. A complete block of the mTOR signalling pathway by the combined deletion of raptor and mTOR in adult skeletal muscle results in increased events of fibre denervation and re‐innervation. Furthermore, raptor–mTOR double knockout (dko) mice show alterations in the expression of calcium‐related genes, leading to an impairment in calcium removal after tetanic stimulation. These alterations, together with a downregulation of genes linked to sarcomere organization, are likely to contribute to the severe muscle weakness and delayed muscle relaxation observed in raptor–mTOR dko mice.